2007
DOI: 10.2193/2006-274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Homogenization of Multiple Sources: Genetic Structure of a Recolonizing Population of Fishers

Abstract: Fishers (Martes pennanti) were extirpated from much of southern Ontario, Canada, prior to the 1950s. We hypothesised that the recent recolonization of this area originated from an expansion of the population in Algonquin Provincial Park, which historically served as a refuge for fishers. To test this hypothesis, we created a sampling lattice to encompass Algonquin and the surrounding area, and we collected contemporaneous DNA samples. We sampled fishers from each of 35 sites and genotyped them at 16 microsatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…Carr et al (2007) showed that the St. Lawrence River has not impeded the range expansion of fishers (Pekania (Martes) pennanti (Erxleben, 1777)) from the Adirondack region of New York, USA, into eastern Ontario, Canada. Likewise, Cullingham et al (2009) showed that the St. Lawrence River has allowed gene flow of raccoons (Procyon lotor (L., 1758)), and thus did not stop the spread of the raccoon rabies virus from New York into southeastern Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Carr et al (2007) showed that the St. Lawrence River has not impeded the range expansion of fishers (Pekania (Martes) pennanti (Erxleben, 1777)) from the Adirondack region of New York, USA, into eastern Ontario, Canada. Likewise, Cullingham et al (2009) showed that the St. Lawrence River has allowed gene flow of raccoons (Procyon lotor (L., 1758)), and thus did not stop the spread of the raccoon rabies virus from New York into southeastern Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…However, high subdivision is not universal among fisher populations. Populations in southern Ontario, Canada have been found to have weak subdivision and high genetic connectivity attributed to high amounts of gene flow along expansion fronts in a growing population [16], [111].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on this dataset revealed one genetic cluster ( K  = 1) [30]. The fisher dataset contained 772 individuals sampled at 34 sites across Ontario, northern New York State, USA, and southern Quebec, Canada, between 2000 and 2003 [8], [29], [31]. There were 7–48 individuals sampled per site (average = 21.2, SD = 7.1).…”
Section: Methodsmentioning
confidence: 99%
“…There were 7–48 individuals sampled per site (average = 21.2, SD = 7.1). The samples were genotyped at 16 microsatellite loci [8]. Previous work with these data suggested 5 genetic clusters ( K  = 5), with 5–11 sites per cluster [8], [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation